Evidence on result-based financing in maternal and child health in low- and middle-income countries: a systematic review - Nigel James; Kenny Lawson; Yubraj Acharya (BMC, 2020)
Abstract Introduction Result-Based Financing (RBF) is an umbrella term for financial mechanisms that link incentives to outputs or outcomes. International development agencies are promoting RBF as a viable financing approach for the realization of universal health coverage, with numerous pilot trials, particularly in low- and middle-income countries (LMICs). There is limited synthesized evidence on the performance of these mechanisms and the reasons for the lack of RBF institutionalization. This study aims to review the evidence of RBF schemes that have been scaled or institutionalized at a national level, focusing on maternal, newborn, and child health (MNCH) programming in LMICs. Methods A systematic literature review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The authors identified and reviewed country-level RBF evaluation reports for the period between January 2000 and June 2019. Data were extracted from both published and gray literature on RBF application in MNCH using a predesigned matrix. The matrix headers included country of application; program setting; coverage and duration; evaluation design and methods; outcome measures; and key findings. A content thematic analysis approach was used to synthesize the evidence and emerging issues. Results The review identified 13 reports from 11 countries, predominantly from Sub-Saharan Africa. Performance-based financing was the most common form of RBF initiatives. The majority of evaluation designs were randomized trials. The evaluations focused on outputs, such as coverage and service utilization, rather than outcomes. RBF schemes in all 11 countries expanded their scope, either geographically or accordingly in terms of performance indicators. Furthermore, only three studies conducted a cost-effectiveness analysis, and only two included a discussion on RBF's sustainability. Only three countries have institutionalized RBF into their national policy. On the basis of the experience of these three countries, the common enabling factors for institutionalization seem to be political will, domestic fund mobilization, and the incorporation of demand-side RBF tools. Conclusion RBF evidence is still growing, partial, and inconclusive. This limited evidence may be one of the reasons why many countries are reluctant to institutionalize RBF. Additional research is needed, particularly regarding cost-effectiveness, affordability, and sustainability of RBF programs.